Social Media Addiction: The Rising Concepts and Issues - Akhtar, Adeeba (Journal of Peace, Development and Communication, 2021)
Social media has become immensely popular during the last decade. The social media activities have occupied a sizable space in the daily lives of individuals around the world specifically among adolescence and young adults. As online communication and interaction is prevailing more than face-to-face interactions, it has started effecting peoples’ communication, language, ways of living, social interests as well as individuals Psychology . The virtual and vibrant in nature, the social media provides an easy access to its users which may lead to over use of social media and consequently may result into social media addiction. The people's Psychological need to remain active on social media platforms may lead them towards the use which is of compulsive nature and in case of excessive use, it may result into symptoms which are traditionally linked to substance-related addictions. This article is aimed at giving brief overview of some of the rising concepts and issues that have emerged in empirical studies during the last one decade regarding social media platforms, their usage and potential for addiction as it is important to establish consensual themes, concepts and issues so that scholars, researchers as well as clinical practitioners can combine their effort for working towards establishing a productive communication system for a reliable assessments of social media addiction and behaviours associated with it. Key Words: Social media, social networking sites, addiction, personality traits, technology, smartphone, fear of missing out, alone together.